Somatic mutations affect key pathways in lung adenocarcinoma - Ding, Li; Getz, Gad; Wheeler, David A.; Mardis, Elaine R.; McLellan, Michael D.; Cibulskis, Kristian; Sougnez, Carrie; Greulich, Heidi; Muzny, Donna M.; Morgan, Margaret B.; Fulton, Lucinda; Fulton, Robert S.; et al. (Nature, 2008)
Determining the genetic basis of cancer requires comprehensive analyses of large collections of histopathologically well-classified primary tumours. Here we report the results of a collaborative study to discover somatic mutations in 188 human lung adenocarcinomas. DNA sequencing of 623 genes with known or potential relationships to cancer revealed more than 1,000 somatic mutations across the samples. Our analysis identified 26 genes that are mutated at significantly high frequencies and thus are probably involved in carcinogenesis. The frequently mutated genes include tyrosine kinases, among them the EGFR homologue ERBB4 ; multiple ephrin receptor genes, notably EPHA3 ; vascular endothelial growth factor receptor KDR ; and NTRK genes. These data provide evidence of somatic mutations in primary lung adenocarcinoma for several tumour suppressor genes involved in other cancers—including NF1 , APC , RB1 and ATM —and for sequence changes in PTPRD as well as the frequently deleted gene LRP1B. The observed mutational profiles correlate with clinical features, smoking status and DNA repair defects. These results are reinforced by data integration including single nucleotide polymorphism array and gene expression array. Our findings shed further light on several important signalling pathways involved in lung adenocarcinoma, and suggest new molecular targets for treatment. Mutations involved in lung cancer In large-sale genomics study, mutations associated with lung cancer, the leading cause of cancer death, were examined in 188 primary tumour samples. More than 600 genes with known or potential links to lung adenocarcinoma were sequenced, of which 26 were mutated at high frequency suggestive of a direct role in carcinogenesis. Sequencing of over 600 genes in a large collection of lung adenocarcinoma samples provides an overview of somatic mutations and signalling pathways altered in cancer genes in this tumour type.